Pengaruh Pengungkapan Laporan Keuangan, Kepemilikan Manajerial, Dan Kepemilikan Institusional Terhadap Manajemen Laba (Studi Pada Industri Farmasi Di Bursa Efek Indonesia Tahun 2009-2012) - Nestri Retno Andari; Yane Devi Anna (Jurnal Akuntansi, 2014)
ABSTRACTEarnings management is the ability to raise or lower the reported earnings in accordance with the wishes. This means that earnings management is a management effort to maximize profits or minimize. Earnings management practices is difficult to avoid because it is the impact of the adoption of the accrual basis in preparing the financial statements. This study aims to investigate the influence of financial statements disclosure, managerial ownership, and institutional ownership to earnings management in the pharmaceutical industry are listed in the Indonesia Stock Exchange 2009-2012. This study is classified in descriptive and causal research. The population is pharmaceutical company that is listed on the Indonesia Stock Exchange the period 2009 to 2012. By using purposive sampling, the samples used in this study amounted to 9 companies. The type of data used in this study is secondary data. Data analysis method is using the normality test, heterocedasticity, autocorrelation test, multicollinearity test, the coefficient of determination tests of significance throughout the regression coefficients simultaneously, tests of significance partial regression coefficients, and hypothesis testing or regression coefficient. The result of this study demonstrate simultaneous and partial results. It can be concluded that there is a simultaneous significant relationship between financial statement disclosure, managerial ownership, and institutional ownership on earnings management with a positive coefficient. While the disclosure of financial statements and managerial ownership does not have a significant effect on earnings management, but has a negative directionKeywords: Financial Statement Disclosure, Managerial Ownership, Institutional Ownership, Earnings Management